Penafsiran Nusyūz Dalam Tafsir Nazarat Fi Kitabillah - Tanjung, Nur Ainun; Rahman, Yenni; Ikhwan, Muhammad (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2021)
Misunderstanding about nusyūz and the steps in overcoming it as in Qs. an-Nisa' verses 34 and 128 can cause domestic violence and can include claims that the Qur'an positions women as always weaker than men. So in this study, the problem of nusyūz is discussed based on the opinion of a female mufassir (Zainab al-Ghazali) who is an activist for women's rights defenders and also the first female mufassir to write a complete tafsir. This research is classified as library research. The primary data source in this study is the tafsir of Nazarat fi Kitabillah and secondary data sources are books, scientific journals and others related to object problems. Nusyūz according to Zainab al-Ghazali in Qs. an-Nisa 'verse 34 and 128 means to exalt. A nusyūz woman is one who exalts herself from her husband and leaves her obligations. And the nusyūz solution that Zainab offers in her tafsiris to give advice,separate the bed (back to back and do not talk when sleeping), giving a light blow. Meanwhile, the husband's nusyz is characterized by the husband turning away and showing bad behavior towards his wife. And the solution is reconciliation. Although she is one of the feminist figures who fight for women's rights, in her tafsir of the problem of nusyūz wives and husbands does not at all show gender bias like what feminists do.